6,12-dihydro-1-benzopyrano[3,4-b][1,4]benzothiazin-6-ones synthesis and mdr reversal in tumor cells - Shah Anamik (ANTICANCER RESEARCH, 1998)
Six 6,12-dihydro-1-benzopyrano[3,4-b][1,4]benzothiazin-6-ones and three coumarins were systematically investigated for reversal of multidrug resistance of bacteria and cancer cells in model experiments. 7-Methylcoumarin was able to eliminate the E. coli plasmid significantly; however, the other derivatives were ineffective. Four of 6,12-dihydro-1-benzopyrano[3,4-b] [1,4]benzothiazin-6-ones had a moderate effect on the multidrug resistance efflux pump of mouse lymphoma cells in vitro. Despite of the similarity of resistance mechanisms of bacteria and tumor cells, the reversal of drug resistance in bacteria and in cancer cells is not uniform because the structure-activity requirements are apparently different.